Treatment of tomato paste wastewater by electrochemical and membrane processes: process optimization and cost calculation - Aliye Şen; Ceyhun Akarsu; Zeynep Bilici; Hudaverdi Arslan; Nadir Dizge (Water Science and Technology, 2024)
This study investigated the treatment of wastewater from tomato paste (TP) production using electrocoagulation (EC) and electrooxidation (EO). The effectiveness of water recovery from the pretreated water was then investigated using the membrane process. For this purpose, the effects of independent control variables, including electrode type (aluminum, iron, graphite, and stainless steel), current density (25–75 A/m2), and electrolysis time (15–120 min) on chemical oxygen demand (COD) and color removal were investigated. The results showed that 81.0% of COD and 100% of the color removal were achieved by EC at a current density of 75 A/m2, a pH of 6.84 and a reaction time of 120 min aluminum electrodes. In comparison, EO with graphite electrodes achieved 55.6% of COD and 100% of the color removal under similar conditions. The operating cost was calculated to be in the range of $0.56–30.62/m3. Overall, the results indicate that EO with graphite electrodes is a promising pretreatment process for the removal of various organics. In the membrane process, NP030, NP010, and NF90 membranes were used at a volume of 250 mL and 5 bar. A significant COD removal rate of 94% was achieved with the membrane. The combination of EC and the membrane process demonstrated the feasibility of water recovery from TP wastewater. HIGHLIGHTS The treatment of tomato paste wastewater via electrocoagulation (EC) and electrooxidation (EO) processes was examined.; The membrane process was used as the post-treatment.; Aluminum and graphite electrodes were chosen for EC and EO, respectively.;